Peranan Guru Akidah Akhlak Dalam Mengembangkan Sikap Spiritual Santri Di Yayasan Al Munawwarah Li Binail Ummah Nagari Mungo Kecamatan Luak Kabupaten 50 Kota - Gilang Prayo Setya; Afrinaldi Afrinaldi; Salmi Wati; Wedra Aprison (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This writing is motivated by the phenomenon from the observations in Nagari Mungo that tend to lead to the negative, such as dating behavior that has been done by many students even though they are still at school, fighting behavior that often occurs to solve problems between individuals that should be resolved in a good way and can be reconcile well. This is not in accordance with the concept of a spiritual attitude which shows one's thoughts, words, and actions that are always carried out based on divine values ​​or religious teachings. This study uses a descriptive qualitative approach. Collecting data in this writing the writer obtained through interviews, observation and documentation. The data source for this writing uses the key informants of the Akidah Akhlak teacher, and the supporting informants are students. Data analysis techniques that the authors do are data reduction, data presentation, and conclusions. Then the data validity technique uses Source Triagulation. Based on the results of the study, it can be understood that the role of aqidah moral teachers in developing the spiritual attitude of students at the Al Munawwarah Li Binail Ummah Nagari Mungo Foundation, Luak District, 50 Kota District has an important role in developing students' spiritual attitudes, namely as role models, teachers, mentors, and motivators.